Modified logistic model with mogration factor to predict the population of purwanegara village in Jawa Tengah, Indonesia - Diandra Chika Fransisca author (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The main objectives of this study are ; to extend the modified logistic model with the migration factor as a function of population ; to apply the modified logistic model with the migration factor as a function of population for predicting the population of Purwanegara village, in Jawa Tengah province, Indonesia ; to validate the modified logistic model with the migration factor as a function of the population through simulation approach.